1988
DOI: 10.1073/pnas.85.16.6152
|View full text |Cite|
|
Sign up to set email alerts
|

Epitope mapping of human factor VIII inhibitor antibodies by deletion analysis of factor VIII fragments expressed in Escherichia coli.

Abstract: Epitopes for antibodies that inhibit factor VIII procoagulant protein were analyzed by deletion mapping of factor VIII protein fragments expressed in Escherichia coli. A human factor VIII cDNA clone was used to generate E. coli expression vectors encoding fragments containing the 80-kDa factor VIII light chain (A3, C1, and C2 domains) and the 44-kDa carboxyl-terminal half of the factor VIII heavy chain (A2 domain). A series of deletions of each fragment was constructed and tested by immunoblotting for the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 20 publications
4
92
0
1
Order By: Relevance
“…6 A) and have demonstrated that the protective effect of phosphatidylserine is most marked for those inhibitors that bind factor VIII light chain determinants in immunoblotting studies (4,5 (12). The epitopes recognized by the light chain inhibitors have been previously localized within the factor VIII C2 domain (7). Since PS-factor VIII interaction is prevented by these inhibitors, it is likely that the phospholipid-binding site is located within the C2 domain ofhuman factor VIII.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A) and have demonstrated that the protective effect of phosphatidylserine is most marked for those inhibitors that bind factor VIII light chain determinants in immunoblotting studies (4,5 (12). The epitopes recognized by the light chain inhibitors have been previously localized within the factor VIII C2 domain (7). Since PS-factor VIII interaction is prevented by these inhibitors, it is likely that the phospholipid-binding site is located within the C2 domain ofhuman factor VIII.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Carol Fulcher kindly determined the epitope specificities ofthe inhibitors by immunoblotting with human factor VIII and thrombin cleaved factor VIII, as previously described (4,5). The factor VIII epitopes bound by the inhibitors and by the murine monoclonal antibody C8 were localized further by immunoblotting with the factor VIII protein deletion fragments described by Scandella et al (7). These fiagments were derived from a cDNA clone of factor VIII, and they were produced in Escherichia coli.…”
Section: Methodsmentioning
confidence: 99%
“…40 Regarding von Willebrand factor, this factor indeed has a protective action against inhibitor development, as demonstrated in an animal model. 41 It binds to the C2 domain of FVIII, which is frequently the target of anti-FVIII antibodies 42 and contains the binding site for phospholipids (PLs). The thrombin cleavage within the C2 domain leads to the release of FVIIIa from its complex and increase in FVIIIa affinity for PLs.…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast, most hemophilic alloantibodies appear to recognize both domains. 10 Most inhibitor antibodies with a C2 epitope inhibit binding of FVIII to both vWF and phospholipid (PL). 11,12 However, a new dominant epitope in the A3-C1 domains has been identified, and some antibodies that recognize this epitope also prevent the association between FVIII and factor IXa (FIXa).…”
Section: Introductionmentioning
confidence: 99%